Just-in-time teaching in undergraduate physics courses: implementation, learning, and perceptions - Dwyer, Jessica Hewitt (Kansas State University, 2015)
Regardless of discipline, a decades-long battle has ensued within nearly every classroom in higher education: instructors getting students to come to class prepared to learn. In response to this clash between teacher expectations and frequent student neglect, a group of four physics education researchers developed a reformed instructional strategy called Just-in-Time Teaching (JiTT). This dissertation investigates the following three areas: 1) the fidelity with which undergraduate physics instructors implement JiTT, 2) whether student performance predicts student perception of their instructor’s fidelity of JiTT implementation, and 3) whether student perception of their instructor’s fidelity of JiTT implementation correlates with student views of their physics course. A blend of quantitative data (e.g., students grades, inventory scores, and questionnaire responses) are integrated with qualitative data (e.g., individual faculty interviews, student focus group discussions, and classroom observations). This study revealed no statistically significant relationship between instructors who spent time on a predefined JiTT critical component and their designation as a JiTT user or non-user. While JiTT users implemented the pedagogy in accordance with the creators’ intended ideal vision, many also had trouble reconciling personal concerns about their role as a JiTT adopter and the anticipated demand of the innovation. I recommend that this population of faculty members can serve as a JiTT model for other courses, disciplines, and/or institutions. Student performance was not a predictor of student perception instructor fidelity of JiTT implementation. Additionally, the majority of students in this study reported they read their textbook prior to class and that JiTT assignments helped them prepare for in-class learning. I found evidence that exposure to the JiTT strategy may correlate with a more favorable student view of their physics course. Finally, according to students, favorable JiTT implementation occurred when instructors reviewed all questions contained within the JiTT assignment during class and when instructors clearly connected JiTT questions to the textbook reading, lesson discussion, and other assignments. The impact of this work rests in its possibility to set the stage for future education studies on the fidelity of implementation of other research-based instructional strategies in various disciplines and how they affect student performance and perceptions.
Keywords: Pedagogy; JiTT; Just in Time Teaching; Higher education; Science Education; Fidelity of implementation; Education, Technology (0710); Pedagogy (0456); Science Education (0714)